Pentingnya Pendidikan Karakter dalam Mencegah Radikalisme di MI Islamiyah Surabaya - Aprilia, Popi; Wardani, Salwa Azelina; Rahayu, Aulia Sagita; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
The modernization era now causes a loss of morale or boundaries between societies in the world. We can know many cultures or technologies that are growing rapidly in Indonesia. Of course, with the role of this development, it can facilitate human activities in everyday life. However, behind this comes the bad effects, for example, the rise of radicalism, intolerance, and so on. If we can't filter it out, we're afraid we might fall into negativity. In this world of education to overcome the adverse effects of modernization, we need to prioritize character education in children, especially in basic education. In this study, researchers will describe how important character education is in the modernization era, the causes of radicalism and efforts to solve it in the school environment, and what programs are relevant to overcome radicalism through character education. This research method uses descriptive qualitative, with collection techniques based on observations, interviews, and literature reviews that are database through google scholar.